2017
DOI: 10.4314/ijbcs.v10i5.26
|View full text |Cite
|
Sign up to set email alerts
|

Les microorganismes dans le maintien de l’équilibre et la réhabilitation des écosystèmes de mangrove pollués par les hydrocarbures. Revue bibliographique

Abstract: RESUMELes mangroves constituent un écosystème particulier. Leur développement est fortement lié à leur fonctionnement. La microflore y joue un rôle de premier plan. Grâce à son activité de dégradation de la matière organique, elle pourvoie, aux organismes supérieurs, les éléments nutritifs d'importance tels que l'azote et le phosphore indispensables à leurs cycles biologiques. Il existe une relation entre la composition globale des microorganismes et la demande en éléments nutritifs. Une simulation artificiell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Solubilization of insoluble phosphorus can be achieved by root phosphatases, but microorganisms also play a significant role, with organic acids or chelates they excrete (Davet, 1996). Many studies have reported that there is a high proportion of phosphate solubilizing microorganisms (PSMs), including bacteria, fungi and Actinomycetes, which live in the plant rhizosphere and play an important role in phosphate solubilization, converting phosphate into soluble compounds for plants (Sujatha et al, 2004;Gravel et al, 2007;Lang et al, 2016).…”
mentioning
confidence: 99%
“…Solubilization of insoluble phosphorus can be achieved by root phosphatases, but microorganisms also play a significant role, with organic acids or chelates they excrete (Davet, 1996). Many studies have reported that there is a high proportion of phosphate solubilizing microorganisms (PSMs), including bacteria, fungi and Actinomycetes, which live in the plant rhizosphere and play an important role in phosphate solubilization, converting phosphate into soluble compounds for plants (Sujatha et al, 2004;Gravel et al, 2007;Lang et al, 2016).…”
mentioning
confidence: 99%